Ethical Challenges in Social Work Practice in Sri Lanka - Bhagya Hithaishi Jayawardana; K Nanayakkara (Asian Social Work Journal, 2018)
Ethical practice is fundamental to any practiced based profession including social work. The social work profession is a diverse one with a mission to promote wellbeing and quality of life for vulnerable people. Despite serving the society it’s also central to promoting social work Ethics to maintain the professional standards and lessen the ethical issues and dilemma’s faced in day today practice. Ethics are really important to any profession, yet a necessity for those rooted in and human services. In the Sri Lankan context, it is disheartening to see how social workers have lost their professional identity with the absence of a professional code of ethics in place. A qualitative research approach was followed to explore and describe the key ethical challenges faced by the social workers in Sri Lanka. Survey method, in-depth interviews and key informants interviews were utilized and analyzed based on purposive sampling method. The data were categorized based on different themes. The finding proves that there is no proper guideline to be followed for the practitioners, particularly in situations of ethical dilemmas and conflicts. Most of the Human Service Organizations have their own set of rules with lesser focus on the code of ethical conduct. The unethical practice unintentionally promotes the malpractice leading to scenarios where organizational set of rules violates the client’s self determination and confidentiality. Although most of the upcoming social work graduates are made aware of the importance of maintaining an ethical conduct, when they join the work force as social workers they face many constraints due to absence of a formal code of ethics. This has resulted most of the social workers not having any obligations to continue an ethical practice hence their practice is inevitably not much embedded in ethics. Thus the study provides an outlook on the ethical challenges faced by the social workers specially working in different sectors in Sri Lanka.